Typical Control System for Adoption and Execution of Management Decisions - Yu, Denisov D.; N, Ph.D., Mylnikova A.; V, Ph.D., Tarasova N.. (International Journal of Engineering and Technology, 2018)
The present article proposes a typical system for managing processes of adoption and execution of managerial decisions, created on the basis of the classical management system with negative feedback. Based on the analysis of the similarities and differences of operational, tactical and strategic decisions, and due to the presence of a single structure and the same functions of management decisions, the possibility of creating a typical system for managing processes of adoption and execution of management decisions is formulated. A management model is proposed that includes units of comparison, blocks of processes adoption, execution and analysis of the execution of management decisions, as well as preliminary, current and follow-up blocks. On the contrary, current and subsequent types of control are used as the inverse negative relationship, on the basis of which the adjustment of the decision-making and execution of managerial decisions, as well as the analysis of the results obtained, is ensured. The implementation of each type of control also includes the organization of preventive control and planning of all verification activities. In the management system for adoption and execution of management decisions, the role of collecting, processing, organizing and storing the information used is emphasized, which is consistent with the basic task of follow-up - accumulation and use of practical experience in making management decisions. This system provides processes for adoption and execution of strategic, tactical and operational management decisions.